Investment in Nigerian tree crops: smallholder production - Laurent, Charles K. (East Lansing, Consortium for the Study of Nigerian Rural Development, 1968)
This is the second CSNRD report on tree crop investment in Nigeria
Bibliography: p. 33.
osc 25/08/2021
Arch
Keywords: Cocoa; Oil palm; Rubber